Studi Gaya Desain Interior Museum Karya Daniel Libeskind - Meliana Hermanto (Intra, 2013)
Daniel Libeskind is one of architect that implement decontructive style in design his building and well known for it’s bold form. Decontructive can be trace as one of modern architecture  branch that sometimes used as alternative style outside the boredome of modern architecture. Libeskind’s work is considered different from most architect, which clearly seen in some of museum he worked on. In every part of his design, form consistency and philosophy approach is a must. It’s what make Libeskind work  has deep meaning. He prefer to deliver strong message and impresion  to the beholder through his  design.